RECONNAISSANCE OF WILD HERB CASSIA TORA L. FOR MINERAL CONTENTS IN DIFFERENT GROWTH STAGES - S.D. PATIL; S.J. WANKHADE; P.K. LABHASETWAR (International Journal of Pharma and Bio Sciences, 2012)
Cassia tora L. (Family- Caesalpiniaceae) an Indian wasteland rainy season weed was evaluated for mineral contents in different growth stages of 15, 30, 45 and 60 days using inductively coupled plasma optical emission spectrometry (ICP-OES) and flame photometer. The mineral concentrations were ranged between 0.05 - 5870 µg g-1 (leaves), 0.21 - 6929 µg g-1 (stem), 0.04 - 8581 µg g-1 (root), 0.26 - 4785 µg g-1 (flower) and 0.55 - 6314 µg g-1 (seed). Seed contained high amount of Co (0.55 µg g-1), Fe (1424 µg g-1), Al (1982 µg g-1) and Na (641.25 µg g-1), while Ni content (1.86 µg g-1) was high in stem of 30 days. Stem of 60-day-old plant contained abundant amount of Cr (6.26 µg g-1), Cu (39.34 µg g-1) and Pb (7.01 µg g-1), while stem of 45-day-old plant consisted high levels of Mn (52.36 µg g-1). Furthermore, elevated mineral contents in leaves of 30 days, 45 days and root of 30 days growth stage were Zn (57.5 µg g-1), B (36.78 µg g-1) and K (8581.25 µg g-1) respectively. Potassium was the prevalent mineral followed by sodium.